Treatment compliance or medication adherence in children and adolescents on ADHD medication in clinical practice: results from the COMPLY observational study - Wehmeier, Peter M.; Dittmann, Ralf W.; Banaschewski, Tobias (Attention deficit and hyperactivity disorders, 2015)
Although the efficacy and tolerability of ADHD medications have been investigated fairly extensively, there are very few data comparing the different types of medication (e.g. psychostimulants, non-stimulants) in terms of medication adherence. The primary research objective of the COMPLY observational study was to evaluate medication adherence (i.e. compliance) over 1 year in children and adolescents with ADHD in a routine clinical setting. COMPLY was a prospective 12-month, observational, open-label study that included children and adolescents, aged 6–17 years, with ADHD. Medication adherence (i.e. compliance) was measured using the Pediatric Compliance Self-Rating (PCSR) instrument and using items 1–4 of the Medication Adherence Rating Scale (MARS). A total of 504 patients were enrolled. At baseline, 252 patients (50.0 %) were prescribed non-stimulant (atomoxetine) medication and 247 patients (49.0 %) were prescribed psychostimulant medication. Both types of medication were prescribed concomitantly in five patients (1.0 %). After 12 months, 123 patients (48.8 %) were taking atomoxetine and 176 patients (71.3 %) were taking psychostimulants. Adherence (PCSR score ≥5) was present in both groups (atomoxetine: 67.5 %; psychostimulant: 74.2 %) throughout the observation period. MARS scores declined over time in both groups (atomoxetine: from 3.7 to 2.9; psychostimulant: from 3.6 to 3.1), indicating a deterioration in adherence. There was no statistically significant difference in terms of medication adherence between the two groups.